2021
DOI: 10.5812/ijhrba.108648
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Attempted Suicide Epidemiology in Sirjan in 2018

Abstract: Background: Prevalence of suicide and attempted suicide has increased due to social, economic, and cultural factors. Objectives: This study aimed to investigate the suicide and attempted suicide epidemiology in Sirjan, Iran, in 2018. Methods: Following a cross-sectional design, suicide attempts and their related factors were investigated in the city of Sirjan in 2018. Data were collected by a researcher-developed checklist and were analyzed using descriptive and analytical statistics (i.e., chi-square or Fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Similarly, Dedic and colleagues [ 53 ] demonstrated that the HAM-D score was the major risk factor of repeated suicide in acutely poisoned patients by logistic regression analysis with (OR: 0.22; 95% CI 0.01–9.48; p < 0.001). Correspondingly, the binary logistic regression in an earlier study from Iran [ 57 ] showed a significant association between suicidal attempts and the existence of previous psychiatric consultation (OR = 4.290; 95% CI 1.19–15.41; p = 0.03).…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Dedic and colleagues [ 53 ] demonstrated that the HAM-D score was the major risk factor of repeated suicide in acutely poisoned patients by logistic regression analysis with (OR: 0.22; 95% CI 0.01–9.48; p < 0.001). Correspondingly, the binary logistic regression in an earlier study from Iran [ 57 ] showed a significant association between suicidal attempts and the existence of previous psychiatric consultation (OR = 4.290; 95% CI 1.19–15.41; p = 0.03).…”
Section: Discussionmentioning
confidence: 73%
“…Based on the findings of studies conducted on completed suicides in different provinces of Iran, the highest prevalence of completed suicide in the general population was related to Gonabad and Bajestan (2011), with 130.0 cases, and the lowest to Tehran (2010), with 0.2 cases per 100,000 people ( 29 , 39 ). Moreover, after examining the prevalence of completed suicides by gender, it was found that the highest rate in men belonged to Ilam (2011) with 24.0 and the lowest rate belonged to Larestan and Gerash (2012) with 1.46 cases per 100,000 people ( 30 , 38 ) ( 33 , 39 ) and, in women, the highest rate belonged to Ilam (2014) with estimated 16.2 cases and the lowest rate belonged to Sirjan (2018) with 0.6 cases per 100,000 people ( 24 , 30 ) ( Table 1 ). The highest proportion of suicide deaths occurred in the age group of 15-24 years (41.6%) and then in the age group of 25-34 years (22.8%) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the rate of suicide attempts was high in Sirjan perhaps due to the geographical status of the city (easy access to drugs, opium, and agricultural pesticides) and hard work conditions in mines. 27 Other studies have also shown that the incidence of suicide in Zarand is much higher than the average global, national, and provincial rate. 28 , 29 Therefore, it seems that suicide is an unsolved problem in this county that needs serious interventions.…”
Section: Discussionmentioning
confidence: 96%